2013
DOI: 10.7326/0003-4819-158-5-201303050-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Associated With Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) has been linked with an increased risk of cognitive impairment and dementia. Purpose To complete a meta-analysis of studies examining the association between AF and cognitive impairment. Data Sources Electronic search of 5 large databases and hand search of article references. Study Selection Prospective and non-prospective studies reporting adjusted risk estimates for the relationship between AF and cognitive impairment. Data Extraction Two abstracters independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
243
1
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(290 citation statements)
references
References 53 publications
11
243
1
17
Order By: Relevance
“…Several different kinds of observational works-such as meta-analyses [12][13][14], reviews [15,16], and cross-sectional [17][18][19], cohort and longitudinal [20][21][22][23][24][25] studies-confirm an independent association between AF and cognitive decline at differing grades of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Several different kinds of observational works-such as meta-analyses [12][13][14], reviews [15,16], and cross-sectional [17][18][19], cohort and longitudinal [20][21][22][23][24][25] studies-confirm an independent association between AF and cognitive decline at differing grades of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and left atrium dilatation are also reported [19][20][21]. The evaluation of cognitive function in every patient with AF is, therefore, indicated due to these complicated relationships, mainly for the purpose of diagnosing subclinical vascular injury and determining the patient's ability to comply with physician recommendations [22].…”
Section: Introductionmentioning
confidence: 99%
“…4 Only recently the relation between AF and cognitive impairment has become the object of investigations, reviews, and meta-analyses. [5][6][7][8][9][10][11] The Figure schematically depicts the possible mechanisms explaining the association. Beyond its well-known effect on stroke, AF may increase dementia risk through mechanisms, such as cerebral hypoperfusion or thromboembolism, causing silent cerebral infarction.…”
mentioning
confidence: 99%
“…8 The risk was highest in patients with stroke (relative risk, 2.70; 95% CI, 1.82-4.00), but still remained significant in the broader population, including patients with or without a history of stroke (relative risk, 1.40; 95% CI, 1.19-1.64), as well as in the analysis restricted to studies that specifically assessed only patients without stroke (relative risk, 1.37; 95% CI, 1.08-1.73). 8 Recent reports from the Cardiovascular Health Study confirmed the effect of incident AF on cognitive decline.…”
mentioning
confidence: 99%
See 1 more Smart Citation